2019
DOI: 10.1002/pros.23878
|View full text |Cite
|
Sign up to set email alerts
|

Low‐serum prostate‐specific antigen level predicts poor outcomes in patients with primary neuroendocrine prostate cancer

Abstract: Background The rarities of primary neuroendocrine prostate cancer (NEPC) and primary adenocarcinoma with neuroendocrine differentiation (NE differentiation) mean that their clinical characteristics have not been fully elucidated. Materials and Methods A total of 449 patients with NEPC, including 352 cases of pure NEPC and 97 cases of NE differentiation, together with 408 629 cases of prostate adenocarcinoma at diagnosis were retrieved from the Surveillance, Epidemiology, and End Results program (2010‐2015). Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…Recent studies on T-NEPC had shown that AR often positively expressed in tumor cells, but despite the AR protein expression in the nucleus, the transcriptional activity of AR was very low, which indicated that epigenetic mechanisms may inhibit AR function ( 16 ). Our study found that the negative PSA expression was an independent prognostic factor, these results were consistent with previous reports ( 17 , 18 ). As T-NEPC and primary neuroendocrine prostate cancer showed similar molecular pathological characteristics ( 1 ), we validated our results using the SEER NEPC database.…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies on T-NEPC had shown that AR often positively expressed in tumor cells, but despite the AR protein expression in the nucleus, the transcriptional activity of AR was very low, which indicated that epigenetic mechanisms may inhibit AR function ( 16 ). Our study found that the negative PSA expression was an independent prognostic factor, these results were consistent with previous reports ( 17 , 18 ). As T-NEPC and primary neuroendocrine prostate cancer showed similar molecular pathological characteristics ( 1 ), we validated our results using the SEER NEPC database.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, NEC patients with PSA levels higher than 4.0 ng/mL accounted for 43.7%, compared with 72.9% of adenocarcinoma patients. This result suggested that except for loss of AR, NEPC patients are typically manifested by the downregulation of PSA ( 28 ). Our investigation was consistent with previous studies, which demonstrated that the PSA marker was usually expressed in adenocarcinoma while SCC, large cell carcinoma, or mixed adenocarcinoma neuroendocrine histology were scarcely expressed PSA ( 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…Low serum PSA levels are an independent negative prognostic factor in PCa. 16 , 17 , 19 PSA‐negative PCa potentially responds poorly to androgen deprivation therapy (ADT). 19 A study using cell lines has demonstrated that cells that express low PSA levels or no PSA preferentially express stem cell genes.…”
Section: Discussionmentioning
confidence: 99%